Secret agent grandma - Stine, R. L. (New York : Scholastic, 1997)
The reader chooses the course of a creepy adventure in which grandma comes to visit and arrives on a train full of angry aliens who are set on taking over the world.
"A Parachute Press book.".
"An apple paperback.".
3.5.
3.5
3-6
Keywords: Plot-your-own stories; Adventure and adventurers -- Fiction; Aliens -- Fiction; Grandmothers -- Fiction; Plot-your-own stories; Adventure fiction; Aliens -- Fiction; Grandmothers -- Fiction; Plot-your-own stories